Influence of micro‐textures on antibacterial behaviour of titanium‐based implant surfaces: In vitro studies. Issue 1 (5th March 2019) - Vadakkumpurath, Shiju; Venugopal, Abhijith Njarakkadu; Ullattil, Sudeep
Abstract : Titanium and its alloys have been widely used as implant materials owing to several favourable properties. Bacterial infections are one of the most prominent reasons for implant failure. Antibacterial drugs are a possible solution to bacterial infection but they kill the normal cells, and in many cases, some traces of the bacteria remain. The bacteria form a biofilm that can act as a conductive medium for regrowth of the bacteria. Customised implant surfaces that inhibit the formation of biofilms and retard the bacterial adherence have a significant potential in the design of futuristic implants. In this study, the antibacterial behaviour of textured titanium Grade‐2 and Grade‐5 surfaces is analysed and compared with a polished surface. The surface topography and its influence on the water wettability were investigated. A culture of Staphylococcus aureus was seeded on the prepared specimen and the bacterial adherence was compared. The results show that the bacterial adhesion and growth are reduced in textured specimens in comparison with a polished specimen. The fewer adherences of bacteria on the textured specimens are attributed to its surface topography and the presence of micro‐dimples, which in turn influence the hydrophilicity of the surfaces.